Penyelesaian Sengketa Tanah Hak Guna Usaha PT. Emha dengan Kelompok Tani Sekar Rukun di Kecamatan Sei Suka Kabupaten Batu Bara - Wahyudi; Tetty Marlina Tarigan (CV Rewang Rencang, 2025)
Land disputes are a common legal problem in Indonesia, especially related to land ownership and use. Conflicts often arise due to overlapping interests between Land Use Rights (HGU) holders and communities claiming rights to the land. One prominent case is the dispute between PT. Emha as the HGU holder and the Sekar Rukun Farmers Group in Sei Suka District, Batu Bara Regency. This study uses an empirical legal approach, a research method that not only examines written legal norms or rules but also examines how the law applies in practice in society. This dispute reflects the complexity of agrarian issues in Indonesia, such as weak land administration, lack of community participation in licensing, and legal uncertainty for small farmers. Dispute resolution has taken administrative, civil, criminal, and even involved independent institutions such as Komnas HAM, showing the importance of reforming agrarian policies that are more in favor of social justice.